How Climate Change is Portrayed in Academic Journals for Teaching Practice - Reinfried, Sibylle; Künzle, Roland; Felder, Susanne (Journal of Geography Education, 2018)
Changes in the global climate are widely discussed in science and society. The question therefore arises as to whether and how climate change is being discussed in periodicals aimed specifically at subject specific education. This paper traces the perception of climate change in these journals as part of an explorative descriptive analysis. Subject of the study were the articles on climate change, climate protection, and climate policy which were published in the period from 2006 to 2016 in eleven German-language journals related to the teaching of Geography, Biology, Chemistry, Physics, and Social Studies at the secondary level. The content analysis of the articles was carried out by means of a previously developed category system whose content and structure is based on the thematic structure of the IPPC reports. In total, 149 articles were identified. Of these, more than 64 per cent were journals relating to Geography. The number of publications varies greatly from year to year. In the years 2009 and 2015, a particularly large number of articles were published, accounting for a total of 44 per cent of the publications covered. Thematically, the publications focused on past and future changes in the climate system and their consequences. In relation to this less well represented were the topics of climate protection and climate policy, such as measures for sustainable development, avoidance of emissions and adaptation to climate change, as well as climate policy conflicts of goals and potential synergies. These findings are significant for future development work aimed at achieving climate literacy.
Keywords: climate change, perception, academic journals for teaching practice, climate literacys, Education for Sustainable Development (ESD)